1, 1′-Diacetyloctamethylferrocene: an overlooked and overdue synthon leading to the facile synthesis of an octamethylferrocenophane. Issue 47 (24th October 2016) - Roemer, Max; Skelton, Brian W.; Piggott, Matthew J.; Koutsantonis, George A.
Abstract : Surprisingly easy access to versatile synthons: high yielding acylation, chloroformylation and intramolecular cyclisation reaction to a ferrocenophane. Abstract : This paper describes the facile preparation of 1, 1′-diacetyloctamethylferrocene (2 ) by acylation of octamethylferrocene (1 ) with acetyl chloride. Chloroformylation with POCl3 /DMF of2 affords a variety of products, including 1, 1′-bis-(1-chlorovinyl)octamethylferrocene (3b ) in high yield. Compound3b cyclises in aqueous sodium hydroxide/DMF to an octamethyl[1, 4]-ferrocenophane bearing a 1-dimethylaminobuta-1, 3-diene-handle (4 ).